Flashbacks From My Past: “Starry Night” - Verbitsky, Irra (Independent Filmmaker, 2008)
Verzio FF Submission This short animated documentary is the personal account of the filmmaker’s childhood in Russia and some of the tragic events that unfolded during World War II, such as the air raid on Kiev or the execution of Jewish families.